1991
DOI: 10.1002/aic.690370704
|View full text |Cite
|
Sign up to set email alerts
|

Periodic forcing of the CSTR: An Application of the generalized II‐criterion

Abstract: Nonlinearities give the opportunity to influence the time average performance of a system by periodic forcing of external parameters. In this article, this concept is applied to the following reactions occurring in a continuous stirred tank reactor:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…When the fermentors are connected in series and the ÿrst fermentor has oscillatory (either periodic or chaotic) behavior then the output of this ÿrst fermentor becomes the non-autonomous input to the second fermentor. Various oscillating, non-autonomous feed inputs have been tried in biological and chemical processes to improve the conversion, yield and productivity of the process (Douglas and Rippin, 1966;Douglas, 1972;Crooke et al, 1980;Sterman and Ydstie, 1991;Henson and Seborg, 1992;Yang and Su, 1993;Balakrishnan and Yang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When the fermentors are connected in series and the ÿrst fermentor has oscillatory (either periodic or chaotic) behavior then the output of this ÿrst fermentor becomes the non-autonomous input to the second fermentor. Various oscillating, non-autonomous feed inputs have been tried in biological and chemical processes to improve the conversion, yield and productivity of the process (Douglas and Rippin, 1966;Douglas, 1972;Crooke et al, 1980;Sterman and Ydstie, 1991;Henson and Seborg, 1992;Yang and Su, 1993;Balakrishnan and Yang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover they have been set in such a way that they form a system which responds favorably to pulsed operation. Specifically, for this system that means that the activation energy for the desired reaction should be higher than that of the undesired reaction (E 3 > E 2 ) to make periodic operation beneficial, as was discussed in section 3.1 and in reference [41]. In practice this means that the surface reaction should be more temperature dependent than the desorption of the reactant.…”
Section: Reaction Parametersmentioning
confidence: 99%
“…Sterman and Ydstie applied the Π-criterion to several basic reaction systems with two competing reactions [41]. They showed that periodic temperature forcing always outperforms the best steady state operation if the activation energy for the desired reaction is higher than that of the undesired reaction.…”
Section: Definition Of Non-steady State Operationmentioning
confidence: 99%
“…Step 2: Using the π-test ( (Bernstein & Gilbert, 1980;Sterman & Ydstie, 1991)) evaluate the intervals [τ i− , τ i+ ] of period values guaranteeing the local improvement of the subsystems objective functions by the periodic operation, and choose…”
Section: Ideal Point Evolutionary Polyoptimal Multiperiodic Optimizationmentioning
confidence: 99%